Development of photocatalytic fuel cell for dye-containing wastewater treatment and electricity generation using zinc oxide immobilized on carbon felt as photoanode - Wan Fadhilah Wan Mohd Khalik (School of Environmental Engineering, 2018)
The main purpose of this research was to degrade organic contaminant, especially azo dyes which simultaneously generate electricity through photocatalytic fuel cell. In order to achieve the objectives, several scopes of this research have been aligned. Reactive Black 5 has been used as main organic contaminants or model fuel in this study to investigate its performance either through degradation or electricity generation in photocatalytic fuel cell. In addition, Reactive Black 5 also one of the common azo reactive dyes that had been used in batik industries in Malaysia. Furthermore, due to effectiveness in degradation and mineralization of azo dyes under solar light irradiation, photocatalyst ZnO was suitable to be used as photoanode in this study. The photoanode was prepared through immobilization process where ZnO was immobilized onto surface of carbon felt by using sodium silicate as binder. The area of carbon felt that covered with ZnO powder was 12 cm2.